Intellectual and behavioural functioning in boys with Duchenne Muscular Dystrophy : neuropsychological testing and correlation with genotype - Donald, Kirsten Ann Mary (Department of Paediatrics and Child Health, 2014)
Includes bibliographical references (leaves 76-82).